CO-EXISTING FLUID AND SILICATE INCLUSIONS IN MANTLE DIAMOND - Tomlinson E.L.; Jones A.P.; Harris J.W. (My University, 2006)
We document the compositions of co-existing silicate macro-inclusions and fluid micro-inclusions in the fibrous coats of eight coated diamonds from the Panda kimberlite (Canada). The mineral inclusions in the diamond coats come from either the peridotite suite (Cr-pyrope, orthopyroxene, olivine and Cr-diopside) or the eclogite suite (omphacite). Therefore, fibrous diamonds grow in the same paragenetic environments as octahedral diamonds. The inclusions document a more fertile source composition (lower Mg# and higher CaO) than for equivalent phases in octahedral diamonds from Panda and worldwide. However, moderate to high Cr2O3 contents in garnet and clinopyroxene inclusions suggest that this apparent fertility is due to a secondary process. Geothermometry of the silicate inclusions yields low equilibration temperatures of 930 to 1010 °C. The co-existing fluid micro-inclusions are dominated by H2O, carbonate and KCl. Fluid inclusions in both the peridotitic and eclogitic samples fall along linear arrays between Fe-Ca-Mg carbonate and KCl. Inclusions in the one eclogitic sample also contain quartz. We suggest that the diamonds have trapped both metasomatised minerals and the metasomatic fluid, and so provide a snap shot of a metasomatic event in the mantle. © 2006 Elsevier B.V. All rights reserved.
Keywords: COATED DIAMOND; FLUID INCLUSIONS; METASOMATISM; SILICATE INCLUSIONS